Profiling analysis of FOX gene family members identified FOXE1 as potential regulator of NSCLC development - Ji, G H; Cui, Y; Yu, H; Cui, X B (Cellular and Molecular Biology, 2016)
Lung cancer is one of the most malignant tumors worldwide with a high mortality rate, which has not been improved since several decades ago. FOX gene family members have been reported to play extensive roles in regulating many biological processes and disorders. In order to clarify the contribution of FOX gene family members in lung cancer biology, we performed expression profiling analysis of FOX gene family members from FOXA to FOXR in lung cancer cell lines and tissue specimens by Real-time PCR, western blot and immunohistochemistry analysis. We found that FOXE1 was the only gene which was over-expressed in six out of eight lung cancer cell lines and human cancer tissue specimens (28 out of 35 cases with higher expression and 7 out of 35 cases with moderate expression). Further investigation showed that MMP2 gene was up-regulated, and autophagy markers such as LC3B, ATG5, ATG12 and BECLIN1, were down-regulated concomitant with the increase of FOXE1. These results implicated that FOXE1 may be an important regulator by targeting autophagy and MMPs pathways in lung cancer development.